2002
DOI: 10.1074/jbc.m207882200
|View full text |Cite
|
Sign up to set email alerts
|

Selective Association of TRPC Channel Subunits in Rat Brain Synaptosomes

Abstract: TRPC genes encode a ubiquitous family of ion channel proteins responsible for Ca 2؉ influx following stimulation of G-protein-coupled membrane receptors linked to phospholipase C. These channels may be localized to large multimeric signaling complexes via association with PDZcontaining scaffolding proteins. Based on sequence homology, the TRPC channel family can be divided into two major subgroups: TRPC1, -C4, and -C5 and TRPC3, -C6, and -C7. Although TRPC channels are thought to be tetramers, the actual subun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
216
1
2

Year Published

2003
2003
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 298 publications
(228 citation statements)
references
References 38 publications
9
216
1
2
Order By: Relevance
“…Two labs have independently demonstrated that mammalian TRPCs assemble exclusively within two subfamilies, TRPC3/6/7 and TRPC1/4/5, irrespective of whether they are expressed heterologously or studied in native environments like brain synaptosomes (Strübing et al 2001;Goel et al 2002;Hofmann et al 2002;Schaefer et al 2002). In contrast to these findings, Strübing et al described a more complex mode of TRPC assembly in microsomes from rat embryonic brain (Strübing et al 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Two labs have independently demonstrated that mammalian TRPCs assemble exclusively within two subfamilies, TRPC3/6/7 and TRPC1/4/5, irrespective of whether they are expressed heterologously or studied in native environments like brain synaptosomes (Strübing et al 2001;Goel et al 2002;Hofmann et al 2002;Schaefer et al 2002). In contrast to these findings, Strübing et al described a more complex mode of TRPC assembly in microsomes from rat embryonic brain (Strübing et al 2003).…”
Section: Introductionmentioning
confidence: 99%
“…For the canonical (classic) members of the family (TRPC) channels several groups describe heteromeric combinations of TRPC subfamily members (Amiri et al 2003;Goel et al 2002;Hofmann et al 2002;Montell 1997;Strubing et al 2001Strubing et al , 2003, but only one group describes a potential Nterminal subunit multimerization domain within the murine TRPC1-β isoform (Engelke et al 2002). Here, the authors find a self-interacting site using yeast-two hybrid analyses of TRPC1β cytosolic constructs.…”
Section: Assembly Signals Of Trp Channelsmentioning
confidence: 99%
“…Experimental evidence for tetramer formation exists for TRPV1, TRPV2, and TRPV5/6 Jahnel et al 2001;Kedei et al 2001). Of the three major subfamilies of TRP channels, TRPV, TRPC, and TRPM, it has been shown that some members within the TRPC and within the TRPV family can form heteromeric channels (Amiri et al 2003;Goel et al 2002;Hoenderop et al 2003;Hofmann et al 2002;Montell 1997;Strubing et al 2001Strubing et al , 2003. In some cases, however, it remains to be seen whether the subunits forming these heteromeric channels in expression systems are indeed coexpressed in the same native cells and results drawn from using concatameric constructs need to be critically evaluated in light of their propensity to form lower order byproducts (Nicke et al 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Obvious candidates in terms of supplementary subunits for TRPC3 are other TRPC species. Heteromultimerization among TRP proteins has repeatedly been demonstrated (Xu et al 1997;Goel et al 2002;Hofmann et al 2002;Strubing et al 2003) and a highly restrictive oligomerization among closely related TRPC species has been suggested (Goel et al 2002;Hofmann et al 2002). One subunit composition that is likely to exist in native tissues is TRPC3/TRPC6 (Dietrich et al 2005).…”
Section: Introductionmentioning
confidence: 99%
“…The concept implies that a given TRPC species is able to associate with other channel and auxiliary subunits to form distinct signaling complexes with a composition dependent on the availability of the complex partners. Potential signaling partners, as identified in functional and protein-protein interaction assays, are other TRPC species (Lintschinger et al 2000;Goel et al 2002;Hofmann et al 2002) as well as scaffold and ion transport proteins (Kiselyov et al 1999;Rosker et al 2004). It is expected that the oligomerization with pore-forming proteins, e.g., other TRPC species, will change the biophysical and pharmacological properties of the permeation pathway, while association with scaffolds and signaling partners that do not contribute to the TRPC pore may alter other features such as activation and coupling to specific cellular functions.…”
Section: Introductionmentioning
confidence: 99%